Secretion of tumor necrosis factor-alpha by mouse peritoneal macrophages in the presence of dental sealers, sealapex and endomethasone - Perassi, Fábio Tobias; Bonetti Filho, Idomeo [UNESP]; Berbert, Fábio Luis Camargo Villela [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Leonardo, Renato de Toledo [UNESP] (Wolters Kluwer, 2004)
After filling root canals, the healing process depends on the chemical composition or physical-chemical properties of the material used, among other factors. All root canal sealers, whether solid or plastic, are foreign matter for the body if they remain in permanent contact with apical and periapical tissues. As a result, the first organic reaction that occurs is an attempt to phagocytize the material. During phagocytosis, macrophages release a large number of cell mediators into the area, among which are cytokines that are essential in intercellular communication and in many physiological and pathophysiological processes. One of these cytokines is tumor necrosis factor-alfa (TNF-α), which acts through links to specific receptors on the cell membrane initiating a cascade of events leading to induction, activation, or inhibition of numerous cytokine-regulated genes in the cell nucleus. The release of TNF-α in a cell culture of mouse peritoneal macrophages incubated with three concentrations (25, 50, and 100 mg/ml) of two endodontic sealers was measured. The solutions containing the calcium hydroxide-based root canal sealer (Sealapex) released fewer units of TNF-α than solutions containing the zinc oxide and eugenol-based sealer (Endomethasone).
Keywords: calcium hydroxide; endomethasone; membrane receptor; plastic; resin; sealant; sealapex; tumor necrosis factor alpha; unclassified drug; zinc oxide; animal cell; animal experiment; cell communication; controlled study; cytokine production; cytokine release; female; mouse; nonhuman; pathophysiology; periodontium; peritoneum macrophage; phagocytosis; plasticity; protein induction; protein synthesis inhibition; regulator gene; solid state; tooth filling; tooth root canal; Animals; Biocompatible Materials; Calcium Hydroxide; Cells, Cultured; Coloring Agents; Dexamethasone; Drug Combinations; Female; Formaldehyde; Gentian Violet; Hydrocortisone; Macrophages, Peritoneal; Mice; Phagocytosis; Receptors, Tumor Necrosis Factor; Root Canal Filling Materials; Salicylates; Thymol; Tumor Necrosis Factor-alpha